(untitled) (Heritage, 2023)
The Six-Day War of 1967 was a war conflict almost unanimously defined in the scientific literature as a school example of preemptive war. The conflict was initiated with Israel’s attack on Egypt and Syria, after prolonged concentration of strong military forces on their common borders by the two countries. In order to prevent joint and coordinated attack on two fronts, Israel destroyed the Egyptian and Syrian Air Force with a carefully planned airstrike in the matter of hours. Since the founding of the State, the Israeli political and military elite have been guided by a collective narrative in addressing serious security threats. This narrative is based on drawing historical parallels with the experience of collective political violence against Jews as a political community in the past. It dictates proactivity in the protection of national interests and national security, and over time it has manifested itself in various ways. The Israeli army, as well as other security branches, have acted preemptively and preventively many times whenever the need to protect the lives and property of Israeli citizens arose. In the eyes of the Israeli political and military elite each of the mentioned above security threats was placed in the context of the German attempt to exterminate the Jews in WW2. Regardless of our attitudes towards the Middle East conflict, the fact remains that Israel’s survival was most threatened in 1948 and 1973, that is, the only two times when Israel was not the first to attack its enemies who grouped against it.